2019
DOI: 10.1177/0892705719870595
|View full text |Cite
|
Sign up to set email alerts
|

Investigations for tensile, compressive and morphological properties of 3D printed functional prototypes of PLA-PEKK-HAp-CS

Abstract: This article reports the experimental investigations for tensile, compressive and morphological properties of 3D printed functional prototypes composed of polylactic acid (PLA) reinforced with poly ether ketone ketone (PEKK), hydroxyapatite (HAp) and chitosan (CS). The PLA-PEKK-HAp-CS composite has wide applications as scaffolds in orthopaedics and clinical dentistry. The tensile and compressive specimens were printed (as per ASTM D638 type IV and ASTM D695) with in-house prepared feedstock filament on commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 34 publications
(34 reference statements)
1
21
0
1
Order By: Relevance
“…Some researchers outlined that increase of infill density with sufficient no. of perimeters for outer wall, the compressive strength of the specimen increases significantly [13]. It has been observed that performance of 3D printed specimen is influenced by the forced air-cooling setup attached to the print head [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers outlined that increase of infill density with sufficient no. of perimeters for outer wall, the compressive strength of the specimen increases significantly [13]. It has been observed that performance of 3D printed specimen is influenced by the forced air-cooling setup attached to the print head [14].…”
Section: Introductionmentioning
confidence: 99%
“…The literature reveals that the use of biodegradable/green waste enhances the mechanical properties and reduces the environmental pollution as well as cost [25][26][27][28][29][30][31]. But hitherto little has been reported on the use of the almond skin in powder form for enhancement of the compressive properties [13,[31][32][33][34]. In this study, composite of PLA and almond skin powder was subjected to compression test (as per ASTM D695), surface hardness (Shore D) investigation for possible use as biomedical scaffold as an extension of previously reported study [35] on preparation of feed stock filament for FFF.…”
Section: Introductionmentioning
confidence: 99%
“…Step 7: Formulate separation measures (S m ) with the help of Euclidean distance, as given in Equations (9) and (10):…”
Section: Equal Weights Methodsmentioning
confidence: 99%
“…[9] The fused deposition modeling (FDM) approach for fabrication of biomedical scaffolds resulted into 15% to 60% reduction of yield strength as compared to hot pressed scaffolds. [10] Further, the 3D printing of a PLA-based scaffold system has achieved maximum compressive strength (CS) at 100% infill speed, 50 mm/min infill speed, and three numbers of external perimeters. [11] It has been ascertained that PLA mixed with 5% wt/vol hydrogel concentration has given stable results of rheology and minimum changes of pH value over scaffolds degradation, promised a good scaffolds for implantation.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional printers are machines used in FFF production. In the printing process, a solid filament, such as polylactic acid (PLA) and acrylonitrile butadiene styrene (ABS), is melted and extruded from a nozzle [1,[12][13][14]. During the printing process in 3D printers, the filament is left layer by layer as it diffuses with the effect of the temperature [15,16].…”
Section: Introductionmentioning
confidence: 99%